Impact of the Florida Birth-Related Neurological Injury Compensation Association (NICA) on Obstetrician and Attorney Practices - Karen W. Geletko; Andrew Hunt; Leslie M. Beitsch (University of North Florida, 2012)
As health reform continues to unfold nationally, one ofthe more dramatic strategies for reform ofthe current medical liability system is to move towards a no-fault compensation system. Although, no state has established a comprehensive no-fault medical malpractice system, the Florida Birth-Related Neurological Injury Compensation Association (NICA) is a unique and rare working model ofa functioning no-fault insurance program. A cross-sectional design was utilized to survey obstetricians and health law attorneys practicing in Florida in 2011 to ascertain their knowledge and opinions of NICA and its impact on practice patterns and defensive medicine. The findings indicate that respondents believe NICA has had no effect on insurance rates among both obstetricians (39.8%) and attorneys(35.3%) nor did obstetricians (52.8%) or attorneys (35.8%) believe it has affected defensive medicine practices. Additionally, the findings further reinforced stereotypic expectations that obstetricians prefer an administrative process (35%) or arbitration (37.5%), while attorneys have a strong preference towards a standard courtroom venue (57.2%). With over two decades of experience with successful implementation of a no-fault obstetrical mal- practice model, Florida has a strong foundation for further bold experimentation. In addition, because of its large population size, the potential for a pilot study expanding the scope ofclinical practice coverage is promising. Further study and experi- mental models should be considered as possible next steps to explore in Florida.